Cervical cancer prevention and treatment in Latin America. Issue 5 (7th February 2017) - Lopez, Melissa S.; Baker, Ellen S.; Maza, Mauricio; Fontes‐Cintra, Georgia; Lopez, Aldo; Carvajal, Juan M.; Nozar, Fernanda; Fiol, Veronica; Schmeler, Kathleen M.
Abstract : Cervical cancer is a preventable disease with a known etiology (human papillomavirus), effective preventive vaccines, excellent screening methods, and a treatable pre‐invasive phase. Surgery is the primary treatment for pre‐invasive and early‐stage disease and can safely be performed in many low‐resource settings. However, cervical cancer rates remain high in many areas of Latin America. This article presents a number of evidence‐based strategies being implemented to improve cervical cancer outcomes in Latin America.